Clinical outcomes of periodontal therapy are not influenced by the ATC/TTC haplotype in the IL8 gene - Corbi, S. C. T. [UNESP]; Finoti, L. S. [UNESP]; Anovazzi, G. [UNESP]; Tanaka, M. H. [UNESP]; Kim, Y. J. [UNESP]; Secolin, R.; Marcaccini, A. M.; Gerlach, R. F.; Orrico, Silvana Regina Perez [UNESP]; Cirelli, Joni Augusto [UNESP]; Scarel-Caminaga, R. M. [UNESP] (Wiley-Blackwell, 2014)
Background and Objective: Although chronic periodontitis (CP) is a multifactorial condition, few studies have investigated the potential association of gene variants with the outcome of periodontal therapy. In a previous study, we reported that variants in the interleukin-8 (IL8) gene were associated with CP in a Brazilian population. The aim of this nonrandomized study was to investigate whether genetic susceptibility to CP, conferred by the presence of the IL8 ATC/TTC haplotype, influences the clinical outcomes of nonsurgical periodontal therapy and the IL-8 protein levels in the gingival crevicular fluid.Material and Methods: Forty-one individuals were grouped according to the presence (susceptible to CP; n = 21) or absence (not susceptible to CP; n = 20) of the IL8 ATC/TTC haplotype. These individuals received nonsurgical periodontal therapy from one periodontist, who was blinded to the genetic status of each patient, and follow up continued for 45 d. The clinical parameters and gingival crevicular fluid samples were collected at baseline and on day 45. The IL-8 levels were determined by an ELISA. The data were subjected to the Mann-Whitney U-test, Wilcoxon and Spearman tests and to multiple logistic-regression analysis.Results: No significant differences between patients with or without the IL8 ATC/TTC haplotype were found for the outcome of nonsurgical periodontal therapy and IL-8 levels. The multiple logistic-regression analysis did not show a statistically significant association between the IL8 haplotype and the variables studied.Conclusion: In this longitudinal clinical study, we observed that neither the outcome of nonsurgical periodontal therapy nor the IL-8 levels were influenced by the IL8 ATC/TTC CP-susceptibility haplotype. Additional studies of CP patients from other ethnic populations are necessary to confirm these results.
Keywords: chemokines; disease susceptibility; genetics; interleukins; periodontal therapy; periodontitis; polymorphism